School Management Strategies for Implementing Deep Learning in Indonesian Junior High Schools - Mulyadi Mulyadi; Warissuddin Sholeh; Mar'atun Sholihah; Sahrizal Vahlevi (Business and Applied Management Journal, 2025)
Improving the quality of deep learning–based instruction at the junior high school level requires the optimization of school management as a foundation for effective educational governance in the era of educational transformation. This study aims to analyze the effectiveness of school management in facilitating the implementation of deep learning and to identify the supporting factors and challenges encountered in Indonesian junior high schools. The research was conducted in eight public and private schools across three provinces—Jambi, South Sumatra, and West Java—using a mixed methods approach with a sequential explanatory design. A total of 120 teachers and principals participated in the quantitative survey, followed by in-depth interviews with 12 key informants to validate the findings. Quantitative data were analyzed using descriptive statistics and simple regression, while qualitative data were examined through thematic coding. The results indicate that optimized school management significantly supports the implementation of deep learning through policy alignment, teacher professional competence, and the availability of learning infrastructure. However, challenges remain in the form of limited facilities and high administrative workload. These findings contribute to the theoretical development of educational management and offer practical implications for improving the quality of learning in Indonesia.